Method for bacteriophage isolation against target campylobacter strains - Carvalho, C. (2010)
Aims: Poultry meat is considered a major source of Campylobacter. This micro-aerobic bacterium is commonly responsible for foodborne illness. This work focuses on the isolation of Campylobacter coli lytic bacteriophages (phages) against target C. coli strains. Methods and Results: A method involving the enrichment of free-range chicken samples in a broth containing the target C. coli strains and salts (CaCl2 and MgSO4) was used for phage isolation. This method allowed the isolation of 43 phages that were active against 83% of the C. coli strains used in the isolation procedure. Approximately 65% of the phages were also effective against Campylobacter jejuni strains. Conclusions: The use of target pathogens in the phage isolation step improves the likelihood of detecting and isolating phages for the control of these specific strains. Significance and Impact of the Study: This technique will be valuable in the context of phage therapy for enriching for phages that are active against specifically identified strains of bacteria, for example from a food poisoning outbreak or epidemic strains resistant to multiple antibiotics. In these situations, using the conventional methods for searching for bacteriophages active for these particular strains can be a time-consuming, if not an unsuccessful process. Using the isolation method described in this manuscript, the particular strains can be added to the enrichment broth increasing the probability of finding phages against them. Therefore, it will shorten the time needed for seeking phages able to lyse target strains, which in most of the cases, because of the rapid increase in antimicrobial-resistant bacteria, is of crucial importance.